Hal-Hal Yang Ada Hubungan Dengan Demam Tifoid Pada Anak Di Beberapa Lokasi Di Wilayah Asia Periode Tahun 2015 Sampai Dengan Tahun 2021 - Amelia, Putri; Madjid, Baedah; Syamsuddin, Fatmawati Annisa (Fakultas Kedokteran Universitas Bosowa, 2025)
Typhoid fever is a systemic infection caused by the bacterium Salmonella enteritidis serovar typhi or abbreviated as Salmonella enterica serovar typhi or Salmonella typhi, which is transmitted through food and drink contaminated with the causative bacteria, with typical symptoms of prolonged fever due to bacteremia due to the invasion of bacteria that cause typhoid fever. Purpose: To find out things that have to do between Typhoid Fever in Children in Several Locations in Asia for the Period 2015 to 2021The research method used is a systematic review by synthesizing the results obtained from ten scientific research journals with a case control research design. The results of the ten studies analyzed showed that there are things related to Typhoid Fever in Children in Several Locations in Asia for the Period 2015 to 2021, namely there was a significant relationship between children's snacking habits (p-value 0.000), children's personal hygiene (p-value 0.000), children's family latrines (p-value 0.000), and clean water supply (p-value 0.000) and there is no a significant relationship between the nutritional status of children (p-value 0.179) and the incidence of typhoid fever in children. Typhoid Fever in Children in Several Locations in Asia for the Period 2015 to 2021 has a significant related with children's snack habits, children's personal hygiene, children's family latrines and clean water supply, and has a non-significant relationship with children's nutritional status.